Permasalahan pemungutan pajak bumi dan bangunan-P2 - Taufiqi, Ahmad Roni; Asari, Fahreza Naafi; Eltari, Miskah Fitriani; Rahim, Sabila Aulia (Maliki Interdisciplinary Journal, 2024)
Indonesia’s Land and Building Tax (PBB-P2) has been a focal point in the context of regional autonomy Law No. 28 of 2009 grants authority to local governments to manage PBB-P2, with the expectation of enhancing local revenue (PAD). However, the implementation of this law faces several challenges, including differing understanding oof tax objects, rates, adn definitions. This research analyzes these constraints by depicing issues in various region, such as Makassar and Madiun. Economic factors, lack of public awareness, and internal governance problems are significant hurdles. To enhance the effectiveness of PBB-P2 collection, it is recommended to increase public awareness, refine regulations, improve human resource quality, and implement stricter monitoring by the central government.